PERANCANGAN APLIKASI PEMINDAI CITRA LEMBAR JAWABAN KOMPUTER (LJK) DENGAN TEKNIK SMART SCAN - Ermundari, Ermundari (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
Computer Answer Sheet is a form for a special paper that will be processed by a computerand scanner. The fact is that the existing scannerComputer Answer Sheet is not flexible, it isintended that its use is only for one type of academic tests,such as examples of the type Ascanner,can only be used for Answer Sheet type A.Computer Answer Sheet Image ScannerApplication Usage with Smart Scan technique based on the basis of the resulting image on thescanner scanning.This application can be used on all types of machines and all kinds of scanner witha particular configuration. Smart Scan technologyutilization in applications designed to use someprocess that can produce the output of thecorrection. The process consists of scanning,image processing with image preprocessing andrecognition area with scanline method. Thescanning process is done by physicaltransformation Answer Sheet into the form of adigital image. This image will be used as input tothe application and will be processed using imagepreprocessing. Preprocessing results in the formof a binary image will be used further in theprocess of introducing area with scanline method.Scanline method is basically a way of introductionpoints/dots to process the object’s entire surfaceby scanning the image horizontally and verticallyto produce the output of characters that can be stored in the database. Based on the resultingdatabase matching answers with the answer keycan be done to produce the output of the value ofthe correction. This study indicate that the designof computer answer sheet image scannerapplication with smart scanning techniques can becorrected the Answer Sheet with 94.5% successrate and the application is considered successful.